2020
DOI: 10.1088/1742-5468/ab6b1c
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of pedestrian flow mixed with wheelchair users through funnel-shaped bottlenecks

Abstract: With the increase of the elderly and disabled in the world, the characteristics of pedestrian flow mixed with wheelchair users has being paid more and more attention.In this study, experiments in funnel-shaped bottlenecks were performed to study the impact of bottleneck shape and the ratio of wheelchair users on the crowd dynamics. It is found that the increase of wheelchairs in the crowd obviously leads to worse moving efficiency and congestion from the escape time, time-space relationship and time headway. U… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…In a similar story to investigate the effect of changing the narrow bottlenecks to funnelshaped bottlenecks on crowd evacuation, Oh and Park [28] explored the evacuation of mice and then simulated that to extract crowd evacuation; they found that by changing the configuration from narrow bottlenecks to funnel-shaped bottlenecks, the efficiency of the bottleneck increased. These results have been confirmed in experimental studies with human participants conducted by different researchers [26,27,29]. It should be mentioned, however, that in all these studies, the funnel-shaped bottlenecks with human participants were located in the middle of the walkway.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In a similar story to investigate the effect of changing the narrow bottlenecks to funnelshaped bottlenecks on crowd evacuation, Oh and Park [28] explored the evacuation of mice and then simulated that to extract crowd evacuation; they found that by changing the configuration from narrow bottlenecks to funnel-shaped bottlenecks, the efficiency of the bottleneck increased. These results have been confirmed in experimental studies with human participants conducted by different researchers [26,27,29]. It should be mentioned, however, that in all these studies, the funnel-shaped bottlenecks with human participants were located in the middle of the walkway.…”
Section: Discussionsupporting
confidence: 62%
“…They concluded that the most efficient bottleneck was the funnel-shaped bottleneck with an angle between 46 • and 65 • . Another recent study by Pan et al [29] investigated the impact of wheelchair users and 4 different angles of funnel-shaped bottleneck on evacuation flow. The narrow point of the bottleneck in each case was 1.2 m and the angles considered were 0 • (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The degree of this impact is also depending on the design (i.e. the angle) of the bottleneck [46]. In general, the underlying dynamics of social groups can indeed have a significant impact in emergency scenarios [44,73].…”
Section: Discussionmentioning
confidence: 99%
“…The adopted technology has the wheelchair to automatically [5]- [7] move in a safe position, and sensor signals are used to make driving easier [8], [9]. These technologies enable efficient wheelchairs to move in crowded places [10]. Such wheelchairs determine the position of movement within the building using 3D simulations to simulate the movement situation for the elderly to practice using wheelchairs effectively [11]- [14].…”
Section: Introductionmentioning
confidence: 99%